Automatisk Nummerpladegenkendelse (ANPG) - Tanja Kammersgaard Christensen (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract The collection of personal data increases with the advancement of investigative possibilities. One of the newer tools used by the police and others in the Nordic countries is ANPR. The wider scope of personal data used in investigations increasingly threatens the right to privacy. This has led to additional focus at both the ECHR and EUC. The current article is based on case law from ECHR and ECJ and focuses on the Danish regulations concerning ANPR. The content of the Danish regulations and the proportionality of the ANPR system are critiqued. The problems cited may also be relevant for other Nordic countries, especially Sweden, where the police are lobbying for the installation of extensive surveillance equipment in police vehicles.